Optical Phenomena and Processes Induced by Ultrashort Light Pulses in Chalcogenide and Chalcohalide Glassy Semiconductors - I. Blonskyi; V. Kadan; A. Rybak; S. Pavlova; L. Calvez; B. Mytsyk; O. Shpotyk (Журнал нано- та електронної фізики)
Time-resolved microscopy study of ablation with femtosecond laser pulses in chalcohalide glass and crystal silicon is presented. The laser pulse energy is deposited into the near-surface layer due to two-photon absorption. The superheated liquid is ejected from the ablation spot under the action of supersonic blast wave. Glass-forming process in chalcohalide glass creates optically smooth spherical surface of the crater due to the action of surface tension forces. As a result, single laser pulse produces microlens, which can be transformed into micromirrors after metal sputtering. The fabricated microoptical elements demonstrate diffraction-limited performance.